A review of IBS implementation in Malaysia and Singapore - Abdul Rahim, Asiah; Latif Qureshi, Sarah (Malaysian Institute of Planners, 2018)
This paper is a review of IBS implementation in Malaysia and Singapore. It investigates the limitations and opportunities in implementation of IBS in Malaysia and Singapore. In Malaysia, Construction Industry Development Board (CIDB) defines Industrialised Building System (IBS) as a construction technique in which components are manufactured in a controlled environment (either onsite or offsite), then transported, positioned and installed into a structure with less additional onsite works. Content analysis is the method adopted in this study. Data is collected from books, journal articles, annual reports and newspaper articles. Studies show that IBS contributes many benefits including labour reduction, cleaner and neater sites, easy installation, fast completion, enhancement of quality finished products and flexibility. Construction industries in countries like Singapore and Malaysia have shifted the construction methods from conventional to prefabrication. In Malaysia, Construction Industry Development Board (CIDB) is still promoting IBS in the private sector, whereas, government sector has successfully adopted IBS. However, in Singapore, Housing and Development Board (HDB) has implemented prefabrication in its construction industry. IBS has many benefits but with these benefits there are some limitations and hindrances as IBS is not widely adopted. This study highlights the benefits and challenges to overcome for the improvement in the implementation of IBS.